16S rDNA-based diversity analysis of bacterial communities associated with soft corals of the Red Sea, Al Rayyis, White Head, KSA. Issue 1 (31st December 2023) - Alsharif, Sultan M.; Waznah, Moayad S.; Ismaeil, Mohamed; El-Sayed, Wael S.
Abstract : Coral reef endogenous to the Red Sea ecosystem is one of the largest globally known living reefs that are remarkably distinctive to constant high temperature and salinity. Coral microbiota is one of the most important prespectives contributing to coral survival in such conditions. Four soft corals endogenous to the eastern Red Sea side at Al Rayyis White Head, KSA were collected and identified as Litophyton sp., Sinularia sp., Xenia sp. and Sarcophyton sp. Soft corals-associated microbiota were investigated using Illumina sequencing of bacterial 16S rRNA genes. Results revealed higher bacterial diversity. Assignment of bacterial reads at the phylum level revealed the predominance of Proteobacteria in all coral-associated microbiotas followed by Bacteroidetes and Firmicutes . At the family level, Litophyton sp. was dominated by Hahellaceae, Staphylococcaceae, Prevotellaceae, Moraxellaceae and Bacteroidaceae, while Xenia sp. was dominated by Hahellaceae and Anaplasmataceae . The microbiota of Sinularia sp. were dominated by Pseudomonadaceae and Enterobacteriaceae . Sarcophyton sp. microbiota mainly include members of Enterobacteriaceae only.